2012
DOI: 10.3233/wor-2012-0387-1790
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a survey to assess workload and fatigue among AMT operators in Mexico

Abstract: Operators of machinery classified as Advanced Manufacturing Technology (AMT) are exposed to high levels of workload and fatigue. However, only few studies have been conducted on this topic in Hispanic-American countries workers. Several instruments be used to assess workload and fatigue; however, only few of them have been adapted to Spanish language. This paper reports on the development and validity testing of a survey instrument in Spanish, aiming to subjectively assess workload and fatigue among AMT operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Integrating the quantity and pace of work (Karasek, 1985), workload is considered "the cost incurred by an individual given their skills while performing a particular level of performance on a task with specific demands" (Arellano, Mejía, Pérez, Alcaraz, & Brunette, 2012, p.1790. PW represents an individual's subjective evaluation of the amount of work.…”
Section: Paradoxical Mechanisms Of Hpwssmentioning
confidence: 99%
“…Integrating the quantity and pace of work (Karasek, 1985), workload is considered "the cost incurred by an individual given their skills while performing a particular level of performance on a task with specific demands" (Arellano, Mejía, Pérez, Alcaraz, & Brunette, 2012, p.1790. PW represents an individual's subjective evaluation of the amount of work.…”
Section: Paradoxical Mechanisms Of Hpwssmentioning
confidence: 99%
“…Workload typically denotes the combination of work quantity and work pace (Karasek, 1985). Given his/her ability, workload means an individual’s cost to work at a specific performance level with specific requirements (Arellano et al, 2012, p.1790). Shirom et al (2010) described workload as “the perception of having too many things to do or not having enough time to do the things one has to do”.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Although this path is not posited by Frone et al, several empirical investigations (Cushman and West, 2006; de Beer et al, 2015; Huang et al, 2022; Reinke and Chamorro-Premuzic, 2014; Sandmeier et al, 2022; Yang, 2004) have shown that work overload leads to burnout. Workload is the cost incurred by an individual, given their abilities, while performing at a specific level in a job that has particular demands (Arellano et al, 2012). Thus, when there is an overload, burnout could be expected.…”
Section: The Integrative Model Of the Work–family Interfacementioning
confidence: 99%